2020
DOI: 10.2147/clep.s251168
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rheumatoid Arthritis as a Risk Factor for Coronary Artery Calcification and Obstructive Coronary Artery Disease in Patients with Chest Pain: A Registry Based Cross-Sectional Study</p>

Abstract: Purpose: To examine the occurrence and severity of coronary artery disease (CAD) in patients with rheumatoid arthritis (RA) compared to non-RA patients in a population referred for coronary computed tomography angiography (CTA) due to chest pain. Patients and Methods: In this cross-sectional study, 46,210 patients from a national CTA database were included. Patients with RA were stratified on serology, treatment with conventional synthetic or biological disease-modifying antirheumatic drugs (DMARDs), and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This study also revealed that the level of increased TAC Agatston scores was negatively correlated with the cumulative dose and cycle of dexamethasone, and logistic regression analysis suggested that dexamethasone was a protective factor for the progression of TAC in breast cancer survivors. However, a study was found that intra-articular or intra-muscular injections glucocorticoid increased the level of coronary artery calcification scores (Tinggaard et al, 2020). In addition, Evans M et al observed that higher cumulative prednisone dose was associated with the incidence of adverse cardiovascular events in rheumatoid arthritis patients (Evans et al, 2011;Karpouzas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also revealed that the level of increased TAC Agatston scores was negatively correlated with the cumulative dose and cycle of dexamethasone, and logistic regression analysis suggested that dexamethasone was a protective factor for the progression of TAC in breast cancer survivors. However, a study was found that intra-articular or intra-muscular injections glucocorticoid increased the level of coronary artery calcification scores (Tinggaard et al, 2020). In addition, Evans M et al observed that higher cumulative prednisone dose was associated with the incidence of adverse cardiovascular events in rheumatoid arthritis patients (Evans et al, 2011;Karpouzas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is a common treatment for breast cancer patients and has been observed to promote coronary and aorta calcification in patients with Hodgkin lymphoma (Apter et al, 2006). Glucocorticoid is frequently used as adjuvant drugs in chemotherapy or endocrine therapy in breast cancer patients, and studies have found that glucocorticoid promoted VC in vivo and in vitro (Kirton et al, 2006;Tinggaard et al, 2020). Furthermore, dexamethasone is the most commonly type of glucocorticoid in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…All four groups were subdivided into main groups and subgroups. For use of DMARD (Disease Modifying Antirheumatic Drug) we applied the Anatomical Therapeutic Chemical code (ATC) and the treatment procedure code as described previously [ 17 ]. The validity of some rheumatic diagnoses in the Danish registries has been investigated earlier, with positive predictive findings of approximately 88% for rheumatoid arthritis [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…All four groups were subdivided into main groups and subgroups. For the use of DMARDS we used the Anatomical Therapeutic Chemical code (ATC) and the treatment procedure code as described previously [17]. The validity of some rheumatic diagnoses in the Danish registries have been investigated earlier, with positive predictive ndings of approximately 88% for rheumatoid arthritis [18] .…”
Section: Methodsmentioning
confidence: 99%